The genetic and molecular origin of natural variation for the fragrance trait in an elite Malaysian aromatic rice through quantitative trait loci mapping using SSR and gene-based markers - Hashemi, Farahnaz Sadat Golestan; Y., Mohd Rafii; Ismail, Mohd Razi; Tengku Muda Mohamed, Mahmud; Harun, A. Rahim; Abdul Latif, Mohammad; Aslani, Farzad (Elsevier, 2015)
MRQ74, a popular aromatic Malaysian landrace, allows for charging considerably higher prices than non-aromatic landraces. Thus, breeding this profitable trait has become a priority for Malaysian rice breeding. Despite many studies on aroma genetics, ambiguities considering its genetic basis remain. It has been observed that identifying quantitative trait loci (QTLs) based on anchor markers, particularly candidate genes controlling a trait of interest, can increase the power of QTL detection. Hence, this study aimed to locate QTLs that influence natural variations in rice scent using microsatellites and candidate gene-based sequence polymorphisms. For this purpose, an F2 mapping population including 189 individual plants was developed by MRQ74 crosses with ‘MR84’, a non-scented Malaysian accession. Additionally, qualitative and quantitative approaches were applied to obtain a phenotype data framework. Consequently, we identified two QTLs on chromosomes 4 and 8. These QTLs explained from 3.2% to 39.3% of the total fragrance phenotypic variance. In addition, we could resolve linkage group 8 by adding six gene-based primers in the interval harboring the most robust QTL. Hence, we could locate a putative fgr allele in the QTL found on chromosome 8 in the interval RM223–SCU015RM (1.63 cM). The identified QTLs represent an important step toward recognition of the rice flavor genetic control mechanism. In addition, this identification will likely accelerate the progress of the use of molecular markers for gene isolation, gene-based cloning, and marker-assisted selection breeding programs aimed at improving rice cultivars.